Visual Culture, Heritage and Identity : Using Rock Art to Reconnect Past and Present - Rozwadowski, Andrzej; Hampson, Jamie, 1973- (Archaeopress archaeology., 2021)
This book presents a fresh perspective on rock art by considering how ancient images function in the present. It focuses on how ancient heritage is recognized and reified in the modern world, and how rock art stimulates contemporary processes of cultural identity-making.